Evaluating the properties of improved asphalt material and hot mixture asphalt by adopting rotational viscosity test and wheel track test - Huda Abd Alwahed Kazim; Ali Fadhil Naser; Zahraa Fakhri Jawad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Scientists and engineers are continually attempting to enhance the performance of asphalt pavements by altering the asphalt. Because of their natural compatibility with asphalt cement as well as their exceptional properties, polymers may offer an excellent opportunity for asphalt modification to extend service life and reduce early distress by enhancing the properties of hot-mix asphalt. This study aims to explain how the various polymers influence the properties of hot mix asphalt with a wet procedure using asphalt produced locally at the Al-Durah refinery and various polymers. Styrene-butadiene-styrene (SBS), polytetrafluoroethylene (PTFE), polyvinyl chloride (PVC), and (PVC+SBS) are examples of these polymers. Three and five per cent of the polymer are utilized for SBS, PTFE, and PVC, respectively. The asphalt cement ratio for (SBS+PVC) was 2.5% by weight at various blending times. The polymer asphalt mixtures are evaluated using Wheel Track tests and then compared to the conventional mixture. The modification of bitumen with polymers enhanced its conventional properties, such as viscosity. In addition, it was determined that the mechanical properties of HMA prepared with PMB samples, as measured by wheel track experiments, improved with increasing polymer contents.